Digitopodium citri sp. nov.; an endophytic species associated with Citrus medica L. var. sarcodactylis from Guangdong Province, China - Liang, Jie-Rong; Senanayake, Indunil C.; Dong, Zhang-Yong; Hongsanan, Sinang; Luo, Mei (Phytotaxa, 2023)
Fingered citron (Citrus medica var. sarcodactylis), is one of the fragrant herbs of the family Rutaceae. This plant is widely cultivated for its medicinal properties, food and flavoring uses, ornamental value, and cultural significance. In this study, we collected fruits of fingered citron in Deqing County, Zhaoqing City, Guangdong Province, China, and several isolates of an endophytic, pigmented hyphomycetes species were obtained. The DNA sequences of our isolates were compared and analysed with those in the NCBI database, revealing that they are closely related to Digitopodium. Maximum likelihood, Maximum parsimony and Bayesian analyses of combined LSU and ITS sequence data were performed to clarify the phylogenetic affinities of the species. Based on the distinctive morphological characters and phylogenetic support, a new species, Digitopodium citri sp. nov. is introduced. The new species is compared with other similar taxa and comprehensive descriptions and illustrations are provided. This is the first endophytic species of Digitopodium.